Prenatal exposure to organophosphorus flame retardants and birth outcomes: A cross-sectional study in an e-waste area in China - Chuyan Zhang; Zheng Ruan; Yifan Dou; Xian Liang Sun; Huadong Xu; Zhaoqiang Jiang; Xia Rao; Xinran Wang; Shoji F. Nakayama; Teruhiko Kido; Jianlin Lou (Ecotoxicology and Environmental Safety)
Organophosphorus flame retardants (OPFRs), widely adopted as substitutes for restricted brominated flame retardants (BFRs), have emerged as significant environmental contaminants in regions burdened by electronic waste (e-waste) recycling activities. Consequently, this study aimed to investigate the relationship between prenatal exposure to OPFRs and infant birth outcomes in an e-waste area. We used programmed-temperature vaporizer gas chromatography-mass spectrometry (PTV-GC/MS) to measure the concentrations of thirteen OPFRs in umbilical cord blood samples from 131 mother-infant pairs in Taizhou. The associations between seven of these OPFRs and infant birth outcomes, including birth weight and birth length, were analyzed. Multiple linear regression (MLR) was used to examine the relationship between each OPFR and the birth outcomes. Additionally, the Bayesian kernel machine regression (BKMR) model was employed to evaluate the impact of mixed exposure to multiple OPFRs on birth outcomes. Both MLR and BKMR analyses revealed significant associations between prenatal exposure to specific OPFRs and infant birth outcomes. Trimethyl phosphate (TMP) was significantly associated with increased birth weight and decreased birth length in newborns overall, with these effects being more pronounced in male infants following gender-stratified analysis. Tri(2-chloroethyl) phosphate (TCEP) demonstrated significant positive correlations with birth length in male infants and birth weight in female infants. Conversely, tripropyl phosphate (TPP) showed a negative correlation with birth length in male infants but a positive correlation in female infants. Furthermore, the BKMR model identified a nonlinear relationship between triethyl phosphate (TEP) and birth outcomes in male infants, suggesting potential interactions among TEP, TMP, TCEP, tributyl phosphate (TBP), and tris(2-chloroisopropyl) phosphate (TCPP). Our findings indicate that prenatal OPFR exposure can cross the placenta and may influence infant growth and development, with distinct gender-specific patterns in an e-waste area in China.